Physical activity and sedentary behavior in patients with systemic lupus erythematosus and rheumatoid arthritis - Legge A (Dove Medical Press, 2017)
Alexandra Legge,1 Chris Blanchard,1 John G Hanly2,3 1Department of Medicine, 2Division of Rheumatology, Department of Medicine, 3Department of Pathology, Dalhousie University and Queen Elizabeth II Health Sciences Center, Halifax, NS, Canada Objective: Patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are at increased risk of cardiovascular disease (CVD). As sedentary behavior and lack of physical activity are known cardiovascular risk factors, we compared habitual activity between SLE patients, RA patients, and healthy control participants.Patients and methods: For this cross-sectional study, RA and SLE patients were recruited from rheumatology clinics at an academic medical center from April 2013 to December 2014. Healthy control participants were recruited through local advertising during the same time period. Habitual activity was measured using a triaxial accelerometer worn during waking hours for 7 consecutive days. Minutes per day of sedentary, light, and moderate–vigorous physical activity (MVPA) were recorded and compared between SLE, RA, and healthy participants using ANOVA.Results: There were 59 participants included in the analysis: 20 SLE patients, 19 RA patients, and 20 healthy controls. Disease activity was quiescent in both the SLE and RA groups. All three groups demonstrated high sedentary behavior (mean ± SD sedentary time for all participants: 10.1±1.3 hours/day; 76.4% total wear time). There were no significant differences between SLE, RA, and healthy participants in time spent in sedentary behavior (p=0.80) or light activity (p=0.17). Total MVPA (mean ± SD, minutes/day) was significantly lower in SLE (34.5±22.7; p<0.001) and RA (41.5±21.3; p=0.005) patients compared to controls (64.9±22.4).Conclusion: SLE and RA patients demonstrate suboptimal MVPA despite well-controlled disease. Given their increased CVD risk, effective interventions are required to improve habitual physical activity levels in both populations. Keywords: systemic lupus erythematosus, rheumatoid arthritis, physical activity, sedentary behavior, accelerometry